Investigation of inert gas washout methods in a new numerical model based on an electrical analogy - Schmidt, Christoph; Hatziklitiu, Wasilios; Trinkmann, Frederik; Cattaneo, Giorgio; Port, Johannes (Medical & biological engineering & computing, 2025)
Inert gas washout methods have been shown to detect pathological changes in the small airways that occur in the early stages of obstructive lung diseases such as asthma and COPD. Numerical lung models support the analysis of characteristic washout curves, but are limited in their ability to simulate the complexity of lung anatomy over an appropriate time period. Therefore, the interpretation of patient-specific washout data remains a challenge. A new numerical lung model is presented in which electrical components describe the anatomical and physiological characteristics of the lung as well as gas-specific properties. To verify that the model is able to reproduce characteristic washout curves, the phase 3 slopes (S3) of helium washouts are simulated using simple asymmetric lung anatomies consisting of two parallel connected lung units with volume ratios of frac{1.25}{0.75}, frac{1.50}{0.50}, and {1.75}{0.25} and a total volume flow of 250 ml/s which are evaluated for asymmetries in both the convection- and diffusion-dominated zone of the lung. The results show that the model is able to reproduce the S3 for helium and thus the processes underlying the washout methods, so that electrical components can be used to model these methods. This approach could form the basis of a hardware-based real-time simulator.
Online veröffentlicht: 07. Oktober 2024
Gesehen am 07.01.2025